Modeling and optimizing synthesis of irreversible gel by sol-gel using experimental design. (2nd January 2020) - Driouich, Anas; El Hassani, Safae El Alami; Labjar, Houda; Kassbi, Soukaina; Kambuyi, Toussaint Ntambwe; Britel, Ouafae; Sallek, Brahim; Digua, Khalid; Chroqui, Razane; Chaair, Hassan
Abstract: Geopolymers are considered as an alternative solution of portland cement. The setting of these materials depends on the gelling reaction of sodium silicate, which can lead to the formation of three types of gels; irreversible gel that has interest and no interest gels (reversible and a non-gelling solution). Obtaining an irreversible gel depends on several parameters. In order to control the influence of these parameters on the development of irreversible gel, a central composite design with 23 experiments is employed to improve the irreversibility (Irr) and the variation of the gelling time according to the following parameters (concentration of sodium silicate, concentration of hydrochloric acid and the volume of hydrochloric acid added), while considering their square and rectangular interactions. Optimization of the model by reports to the factors shows that in order to obtain an irreversible gel, the optimal gelling time should be between 10 and 45 min with an acid concentration varying between 1.20 and 1.40 mol/L and a concentration of sodium silicate between 1.70 and 1.80 mol/L with addition of 12.5 mL of hydrochloric acid to the alkaline solution. Graphical Abstract: